Bumblebee Honey in the Nordic Countries - Svanberg, Ingvar; Berggren, Åsa (Ethnobiology Letters, 2018)
Research in historical ethnobiology can provide information about little known and seemingly insignificant practices in the past. The utilization of insect products as a foodstuff is a rare custom in Europe and data on this practice are scarce. From Nordic countries, we have information about producing ant schnapps with the help of the red wood ant, Formica rufa L., which has been used both as a remedy and as a drink. Honey and beeswax were once gathered in the forests from wild honey bee colonies, but have been replaced with products from the domestic honey bee, Apis mellifera L. Another product, once a well-known and appreciated sweet, especially among children, was nectar gathered from bumblebee nests. Collecting the nectar from bumblebee nests is an activity that has been practiced within living memory in many parts of the Nordic countries. This seems to be an ancient practice dating back at least a millennium that has survived until recently. It is an example of how methods and sources established within historical ethnobiology can be used to gain knowledge on the past as well as possible future uses of available biological resources.